Interactive Learning as a Tool for Activating Educational-Creative Activities of Basic School Students - Askar Zhibek Bauyrzhankyzy; Kalieva K. M. (Theoretical Hypotheses and Empirical Results, 2025)
Abstract This study examines the impact of interactive learning on fostering creativity among basic school students. Specifically, it explores how interactive learning activities, such as group work, gamification, and role-playing, influence students’ creativity in terms of idea generation, flexibility in problem-solving, and originality. Quantitative research design was employed with 30 Grade 7 students (aged 12-13) from two schools. Data were gathered through structured questionnaires. The findings indicate that interactive learning methods enhance students' creative thinking but are hindered by challenges such as time constraints, resource shortages, and collaboration difficulties. The results suggest that interactive learning can be an effective tool for creativity development in schools, but further research is needed to explore its long-term impact and how to overcome the barriers identified.